Managing medication in schools. Issue 12 (21st November 2005) - Reading, R
Abstract : Increasing numbers of children and young people are prescribed medication to be taken in school. This article discusses general principles of prescribing medication for use in school, specific conditions for which medicines may be prescribed, and the key role of nurses in liaison with schools. Decisions about prescribing medication for use in schools do not only depend on evidence of therapeutic effectiveness but need to take into account other social and educational benefits and harms that may occur when children need to use medication in school.